Effect of individual variations in genes related to dopamine brain transmission on performance with and without rewards during motor sequence and probabilistic learning tasks in children and young adults with and without cerebral palsy - Barrett Dryden; Jesse Matsubara; Eric Wassermann; Hans Forssberg; Diane L. Damiano (PLoS ONE, 2025)
Children with cerebral palsy (CP) often participate in training to improve mobility, hand function and other motor abilities. However, responses to these interventions vary considerably across individuals even those with similar brain injuries, ages and functional levels. Dopamine is a neurotrasmitter known to affect motor skill acquistion in animals and humans and may be influenced by individual variations in genes related to brain transmission of dopamine. To evaluate potential genetic influences on learning in young people with and without CP, we calculated individual dopamine-related gene scores and compared these to the ability to learn two different tasks, an implicit sequence learning task and a probablistic classification task. Each task was also administered in an unrewarded condition and a rewarded one known to increase circulating levels of dopamine. The main finding was an interaction between gene score and condition for the sequence task such that those with low gene scores were poorer learners without rewards but responded positively to rewards whereas the converse was true for those with high gene scores. This is the first prospective study in CP suggesting that genetic variability may influence neurorehabilitation outcomes and could potentially be modulated using rewards or medications for those with poorer learning at baseline, thus promoting more personalized approaches to enhancing motor training in CP and other neurological conditions.